Ethanol steam reforming using Ni(II)-Al(III) layered double hydroxide as catalyst precursor - Mas, Verónica (2008)
A preliminary kinetic study of ethanol steam reforming using a Ni(II)-Al(III) lamellar double hydroxide (LDH) as catalyst precursor is carried out within the region of kinetic rate control. Ni(II)Al(III) precursor is synthesized by means of homogeneous precipitation by urea. Under highly diluted feed conditions used in the kinetic experiments, products obtained are H2, CO, CO2 and traces of CH4. A parallel kinetic set is capable to describe the product distribution obtained. Assuming power law, kinetic parameters were fitted for both reactions involved in an operation range where reaction rate was assumed to be independent of water concentration. Ethanol orders were found to be lower than 1. A maximum ethanol conversion was found as a function of water concentration in the feed. Experiences with different methane concentrations showed that ethanol conversion decreases when methane concentration increases. These results reveal the existence of competitiveness between both reactants and methane to be adsorbed in the same type of active site. In order to complete the kinetic study, the Langmuir Hinshelwood model is expected to apply.